Mass transfer characteristics at cathode/electrolyte interface during electrodeposition of nickel microcolumns with various aspect ratios - Dong, Yanzhuo; Jiang, Bingyan; Drummer, Dietmar; Zhang, Lu (Journal of Micromechanics and Microengineering, 2023)
The filling behavior of electrodeposited microcolumns is strongly influenced by the mass transfer characteristics at the cathode/electrolyte interface. This study aims to elucidate the influence of the mass transfer characteristics (ion supplementation via diffusion and ion consumption via deposition) on the electrodeposition of microcolumns, thus providing feasible solutions for improving void defects with different feature sizes. The results indicate that ion consumption plays an important role in the mass transfer within large-width microcavities (100 μm). For large-width microcolumns, longer electroforming times lead to higher ion consumption, resulting in nonuniform ion concentration distribution, and consequently uneven deposition rates along the microcavity wall. In microcavities with high aspect ratio (5:1), ion supplementation plays a major role. The low ion supplementation rate does not support a uniform deposition, resulting in a large void defect and a low filling ratio in the deposited microcolumns. Therefore, reducing the ion consumption rate by decreasing the current density from 1 A dm-2 to 0.25 A dm-2 can effectively increase the filling ratio in large-width microcolumns with no significant effect on high aspect ratio microcolumns. On the contrary, the pulse reverse current (forward pulse current density 1 A dm-2, reverse pulse current density 2 A dm-2, frequency 1 Hz, forward pulse duty cycle 0.9) can increase the filling ratio in the high aspect ratio microcolumns by accelerating ion supplementation through dissolution of the deposited layer. By further increasing the reverse pulse current density from 2 A dm-2 to 6 A dm-2, void defects can be completely eliminated and even void-free deposition of high aspect ratio microcolumns (5:1) can be achieved.
CRIS-Team Scopus Importer:2023-09-15
Keywords: electrodeposited microcolumns; filling ratio; ion consumption; ion supplementation; mass transfer